From competence when doing to accountability when acting: ethics and research in Human Sciences (Práxis Educativa, 2017)
This paper proposes a discussion of the relation between Science and ethics, highlighting the ethical dimension implied in the scientific research. Qualitative research was developed based on ´bibliographic survey. The theoretical background addresses modern science through a historical-conceptual approach, showing the troubled consequences of its epistemological totalitarianism which overlaps the competences when doing (techné) with the accountability when acting (práxis). Next, it defines the concept of ethics and presents its levels: ethics of norms, principles and relations, showing their respective depths from the standpoint of the human sense underlying it. Finally, the paper summarizes the process that results in the formation of Research Ethics Committees (CEP, Brazilian Portuguese abbreviation). The results revealed the possibility to question the epistemological relevance of the scientific research regulation in the Human and Social Sciences by a Committee guided by paradigms of the biomedical areas. The conclusion reflects upon the need of a new organization of the Research Ethics Committees based on the epistemological specificity of the areas of the projects submitted to regulation. Keywords: Science. Technique. Research. Ethics. Human Sciences.